Long-term Bowel function and pediatric health-related quality of life after transanal rectal mucosectomy and partial internal anal sphincterectomy pull-through for Hirschsprung Disease - Zhang, Zhen; Li, Qi; Li, Bo; Alganabi, Mashriq; Li, Long (Frontiers in Pediatrics, 2023)
Background: We have previously shown that a novel modification of transanal rectal mucosectomy and partial internal anal sphincterectomy (TRM-PIAS) for Hirschsprung disease have the advantage of low postoperative Hirschsprung associated enterocolitis. The controlled long-term follow-up studies evaluating bowel function and QoL remain unclear. Methods: Between Jan 2006 and Jan 2016, 243 Patients underwent TRM-PIAS older than 4 years were included, while experienced redo surgery because of complication were excluded. Patients were compared with age- and gender-matched 244 healthy children each randomly selected from the 405 general population. The enrollee was investigated for questionnaires on bowel function and Pediatric Quality of Life Inventory (PedsQL, age <18 years). Results: One hundred and ninety-nine (81.9%) patients’ representatives for the entire study population responded. The mean age of patients was 84.4 months. Compared with controls, patients reported impairment of hold back defecation, fecal soiling, and the urge to defecate (P < 0.05), and no significantly different in fecal accidents, constipation and social problems. With advancing age, the total BFS of HD patients improved, with a tendency close to the normal level beyond 10 years old. But, after grouped according to presence or absence of HAEC, the non-HAEC group experienced more dramatic improvement with age increasing. Conclusions: Compared with matched peers, significant impairment of fecal control prevails after TRM-PIAS in HD patients, but bowel function improve with age and recovery faster than conventional procedure. It should be emphasized that post-enterocolitis is a high-risk signal for delayed healing.